Comparison of the Incident Solar Energy and Battery Storage in a 3U CubeSat Satellite for Different Orientation Scenarios - Sanchez-Sanjuan,Sergio (2016)
ABSTRACT In CubeSats, because the size is limited, the estimation of the incident solar energy according to the orbital parameters and satellite attitude is more critical for the design process of the electrical power system. This estimation is helpful either for sizing of the power sources and energy storage or for defining the operation modes of the CubeSat with the energy available. This paper describes the kinematic and dynamic equations to derive the CubeSat attitude; similarly, the mathematical models of solar cells and batteries are also derived to calculate the energy harvested and stored. By determining the attitude of a 3U CubeSat over one orbit, we estimated the incident solar energy and thus the energy generated by the solar cells and energy stored in batteries when a direct energy-transfer architecture is used. In addition, these estimations where performed for three orientation scenarios: nadir-pointing, Sun-pointing and free-orientation. The estimated incident average solar energy for the three scenarios indicated that the Sun-pointing and free-orientation scenarios harvest more energy than the nadir-pointing one. This estimation is also helpful to predict the state of charge of the batteries in standby mode, allowing for determination of the time required for charging the batteries and, hence, the operating modes of the CubeSat. We expect to include the consumed energy while considering all of the operating modes of the satellite as well as different orbital parameters.